Jurisdiction of International Insurance Contract Disputes - Kheiri, Murtada Abdalla (Dirasat: Shari’a and Law Sciences, 2020)
This research deals with the issue of jurisdiction for international insurance contract disputes. The research aims to clarify the jurisdiction of the international insurance contract in the event of an agreement to specify it by the two parties to the contract, as well as in the event that it is not specified. The study adopted the descriptive, comparative and analytical approach in analyzing and describing the legal norms contained in the French and Emirati legislation as well as contained in international agreements then comparing between them. This study concluded that there is a difference between the UAE legislator, which stipulates the jurisdiction of the UAE courts if the obligation has arisen, been implemented, or will be implemented on the UAE territory, regardless of the nationality of the contracting parties. The French Civil Code stipulated in advance that the obligation had been entered into with a French national. The study recommended that the international jurisdiction of national courts should be unified in international insurance contract disputes, provided that these jurisdictions are independent of the laws of the state itself without subordinating to it in a way that does not affect the sovereignty of these countries.